Malnutrition in Chronic Pancreatitis: Causes, Assessment Methods, and Therapeutic Management - Agnieszka Madro (Canadian Journal of Gastroenterology and Hepatology)
Purpose. In recent years, more and more emphasis has been placed on early diagnosis and adequate treatment of malnutrition in the course of chronic diseases (CP). One of these diseases is chronic pancreatitis in which malnutrition may develop as a consequence of abdominal pain, vomiting, diarrhea, and alcohol abuse. The aim of this review paper is recognized if we can improve the nutritional status of patients with CP. Methods. This paper is based on systematic literature review according to the PubMed. Results. One of the most important problems is lack of “gold standard” in screening of nutritional status in patients with CP, especially in outpatient clinics. Another problem is preventing malnutrition in these patients and beginning treatment already at significant stages of disease. To prevent malnutrition you must first recognize the causes of malnutrition in CP, adequately assess its severity using one of available questionnaires and then apply the appropriate therapeutic management. At each visit, remember to assess the nutritional status of the patient, including laboratory markers and anthropometric measurements. Patients should be advised to stop smoking and drinking alcohol and to use adequate enzyme supplementation. Conclusion. Patients with CP should be led by a team of gastroenterologist, diabetologist, and psychologist and consulted by a dietitian, specialist of pain treatment, and surgeon.